Antibacterial Activity of Metanol Extract and n-Butanol Fraction of Euphorbia milii Leaves Against Staphylococcus aureus - Dia Ul Aulia; Agriana Rosmalina Hidayati; Dewi Suryani (Jurnal Biologi Tropis, 2023)
Euphorbia milii is a common garden plant and its leaves have antibacterial activity, due to the presence of saponins, flavonoids, and tannins. As there is an increasing antibiotic resistance to Staphylococcus aureus, there is potential for E. milii as a new antibacterial candidate. The purpose of this study was to determine secondary metabolites of saponins, flavonoids, tannins and to determine the antibacterial activity of E. milii leaves in inhibiting the growth of Staphylococcus aureus (in vitro). Simplisia was extracted by sonication method, then fractionated with a separatory funnel. Extracts and fractions were analyzed qualitatively by tube test and thin layer chromatograpy (TLC). The antibacterial activity of methanol extract (320; 160; and 80 mg/ml) and n-butanol fraction (32; 16; and 8 mg/ml) was tested by disc diffusion method. The results of qualitative test showed that the extracts and fractions were positive for saponins, flavonoids, and tannins.  In antibacterial test, extract at a concentration of 320 mg/ml was able to inhibit bacterial growth with moderate activity category (6.5 mm). Extracts at 160 mg/ml and 80 mg/ml, as well as n-butanol fractions at all concentration showed weak antibacterial activity (<5 mm). Theseresult suggest that the extracts and fractions positively contain metabolites of saponins, flavonoids, and tannins. The extracts and fractions were able to inhibit the growth of staphylococcus aureus, but the activity was not greater than the positive control.